2020
DOI: 10.1021/jacs.0c10369
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Modified ZnO–Au Enabling Alkoxy Intermediates Formation and Dehydrogenation for Photocatalytic Conversion of Methane to Ethylene

Abstract: Photocatalysis provides an intriguing approach for the conversion of methane to multicarbon (C 2+ ) compounds under mild conditions; however, with methyl radicals as the sole reaction intermediate, the current C 2+ products are dominated by ethane, with a negligible selectivity toward ethylene, which, as a key chemical feedstock, possesses higher added value than ethane. Herein, we report a direct photocatalytic methane-to-ethylene conversion pathway involving the formation and dehydrogenation of alkoxy (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 58 publications
(107 reference statements)
11
180
1
2
Order By: Relevance
“…[ 26 ] Furthermore, the adsorption configuration of methane molecules on the surface of photocatalyst can be rationally modulated by regulating the parameters of defects, which is highly beneficial for efficiently converting methane into desired products. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Furthermore, the adsorption configuration of methane molecules on the surface of photocatalyst can be rationally modulated by regulating the parameters of defects, which is highly beneficial for efficiently converting methane into desired products. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…In arecent breakthrough, Jiang et al discovered that ah ybrid of aZ nO base and Pd single atom modified Au nanoparticles (AuPd-ZnO) facilitates the formation of C 2 H 4 by ap hotocatalytic NOCM. [79] Theo ptimal AuPd 2.7 % -ZnO catalyst achieves amethane conversion of 67 mmol g À1 h À1 with as electivity of 39.7 %a nd 54.9 %f or C 2 H 6 and C 2 H 4 , respectively.D uring the photocatalytic process,m ethane first adsorbs onto the ZnO and dissociates into CCH…”
Section: Non-oxidative Coupling Of Methane (Nocm)mentioning
confidence: 98%
“…Av ariety of excellent studies focus on the promoted activities of plasmonic metal/semiconductors hybrids in the photocatalytic conversion of CH 4 . [17,29,30,37,45,[76][77][78][79][80] Li et al achieved the plasmon-induced photocatalytic coupling of methane and carbon dioxide to ethene over ah ybrid of Ag nanoparticles and TiO 2 . [80] Irradiation of the Ag nanoparticles by visible light leads to the generation of hot electrons and holes as ar esult of the strong LSPR effect.…”
Section: Metal/semiconductor Hybridmentioning
confidence: 99%
“…As a result, a methane conversion of 536 μmol g −1 and a C 2 + compounds selectivity of 96% (39.7% C 2 H 4 and 54.9% C 2 H 6 in total produced C 2 + compounds) was obtained using the optimized AuPd 2.7% /ZnO photocatalyst after 8 h of irradiaton. Based on in situ characterizations, it was revealed that methane molecules were first dissociated into methoxy on the surface of ZnO under the assistance of Pd and the methoxy intermediates were further dehydrogenated and coupled with methyl radical into ethoxy, which were subsequently converted into ethylene through dehydrogenation ( Jiang et al, 2021 ).…”
Section: Heterogeneous Photocatalysts For Methane Conversionmentioning
confidence: 99%